Dostosowania polskiej polityki celnej do wymagań Unii Europejskiej - Adamczyk, Marzena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The accession to the European Union had a great influence on Polish economy and politics. One of the most important aspects of accession was adapting customs policy to the standards of EU. This article presents processes that took place in Polish customs policy, in particular shows changes in customs law and customs administration. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 20-31